PENGEMBANGAN MEDIA PERMAINAN ENGKLEK KARTU BERGAMBAR UNTUK PENYUSUNAN KALIMAT SEDERHANA PADA ANAK USIA 5-6 TAHUN DI SUKADANA KAB. KAYONG UTARA - Andini, Weri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to develop a picture card engklek game media to train simple sentence composition in children aged 5- 6 years so that they can determine the level of attractiveness and suitability of use, as well as find out students' responses after using this picture card engklek game media.The research method adopts the development model developed by Borg and Gall. The research uses the following eight steps: (1) potential and problems, (2) data collection, (3) media design creation, (4) media validation, (5) product revision, (6) product trial, (7) revision product, (8) final product. The data collection tools used are: material expert questionnaire and media expert questionnaire to determine the suitability of the product, student response questionnaires are used to determine the attractiveness of the product. The target of research and development of this media is ages 5-6 years.The results of the research that has been developed have obtained a design in the form of a picture card engklek game media for composing simple sentences for children aged 5-6 years, obtaining a feasibility percentage of 81.4% by media experts. The feasibility percentage from material experts is 92% and limited trials have been carried out with a percentage of 86.7%. Based on the results of the description above, the product developed by the researcher is suitable for use as a learning medium.